Optimizing Distance Education with Emotionally Intelligent Decision Support Systems - Murtadha N. Rasol; Salah M.M.Alghazali; Wisam K. Madhloom Aljeazna (International Journal of Computational and Experimental Science and Engineering, 2025)
This article discusses the rapid development of emotional artificial intelligence and its significance in distance education. It highlights the necessity of considering students emotions to enhance educational quality. The analysis shows that emotions are reactions to stimuli and help the body adapt, with facial expressions being a universal method to express emotions. These expressions can be encoded using a facial movement coding system, simplifying the process of reading emotions. Additionally, the article also examines the influence of personality types on emotions and presents existing classifications of personality types. A functional model has been developed to organizing personalized distance education, integrating a decision support system within the LMS that considers students’ emotional states. furthermore, a mathematical model for managing the distance education process has been created, taking into account students’ emotional information, focusing on five primary emotions and four personality types. The article details the development of an algorithm for providing emotional support to influence students’ emotional states, which has been implemented in the decision support system for distance education. Enhancing distance education presents significant opportunities, such as a personalized learning, reduced stress, increased motivation, and efficiency all contributing to a higher quality of education.